The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Trois perspectives lesbiennes féministes articulant le sexe, la sexualité et les rapports sociaux de sexe : Rich, Wittig, Butler - Brossard, Louise (Université du Québec à Montréal, 2004)
Keywords: IREF; approches et analyses; discipline; genre; hétérosexisme; identités; identités LGBTQIA2+; lesbianisme; mémoires/thèses; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

L'hermaphrodite et la bisexualité à l'épreuve du droit dans l'antiquité - Cantarella, Eva (Diogène, 2004)
Keywords: LGBTQIA2+; androgynie; antiquité; approches et analyses; bisexualité; cours; discipline; discours dominant; europe; grèce; grèce antique; his4860; homosexualité; identités LGBTQIA2+; intersexuation; inégalités; moeurs sexuelles; mythologie; patriarcat; premier cycle; périodes historiques; rapports sociaux; rome antique; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Évaluation de l'implantation d'un projet d'éducation à la sexualité en regard des rôles et stéréotypes sexuels dans deux écoles primaires situées en Montérégie - Caron, Françoise; Moore, Danièle (Agence de développement de réseaux locaux de services de santé et de services sociaux de la Montérégie (Québec), 2004)
L'implantation du nouveau programme de formation de l'école québecoise et la redéfinition de l'entente de collaboration entre le ministère de l'Éducation du Québec et le ministère de la Santé et des Services sociaux sont la toile de fond de ce projet. En effet, dans le cadre de ce projet d'éducation à la sexualité, les élèves sont amenés à developper différentes compétences disciplinaires et transversales tout en abordant des ntions reliées aux rôles et stéréotypes sexuels. De plus, la réalisation des activités pédagogiques auprès des enfants repose sur la participation des enseignants et des enseignantes et implique la collaboration let le soutien des infirmières scolaires. Les processus d'adoption et de mise en oeuvre du projet ont été évalués pour connaître les conditions réussite de l'implantation dans deux écoles pilotes de la Montérégie. Le présent rapport rend compte des résultats de cette évaluation. Ceux-ci serviront à améliorer le guide pédagogique et à favoriser l'implantation des activités dans d'autres milieux. De plus, les résultats et les recommandations présentés dans ce rapport sont importants, non seulement pour la mise en oeuvre de ce type d'intervention reliée à l'éducation à la sexualité, mais aussi pour d'autres projets de prévention et de promotion de la santé qui pourraient s'inscrire dans le contexte d'une approche d'École en santé.
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; discipline; montérégie; périodes historiques; québec; ressource en ligne; régions géographiques; science de l'éducation; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation sexuelle

Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (Critical American studies series, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Porno manifesto - Ovidie (La Musardine, 2004)
Je suis une "travailleuse du sexe", comme diraient mes consoeurs américaines. Et cela, beaucoup de journalistes qui ont écrit des articles sur moi ou m'ont invitée sur des plateaux de télévision semblent l'avoir oublié. Les médias ont beaucoup parlé de mon "discours intellectuel", de ma démarche, parfois de mon féminisme, et trop souvent de mes études de philosophie. Comme s'ils s'étaient raccrochés à des choses rassurantes qui leur permettaient d'oublier ce qui les gênait vraiment et ce qu'ils ne parvenaient pas à comprendre : j'étais, je suis, une femme qui fait des films porno devant et derrière la caméra
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; cycles supérieurs; discours dominant; europe; fem1000; fem7000; france; lit3220; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; témoignage

La grande arnaque : sexualité des femmes et échange économico-sexuel - Tabet, Paola (Bibliothèque du féminisme, 2004)
Dans la majorité des sociétés connues, la sexualité apparaît comme un échange asymétrique et non réciproque entre hommes et femmes, une compensation masculine pour une prestation féminine, un paiement qui peut revêtir les formes les plus variées en échange d'une sexualité transformée en service. Comment se fait-il que les hommes, même plongés dans les situations les plus misérables, peuvent se payer le service sexuel d'une femme - alors que non seulement les femmes n'ont pas, sauf exception, cette possibilité mais de plus n' ont même pas droit à leur propre sexualité ?
Keywords: EDI; approches et analyses; cours; cycles supérieurs; discipline; division sexuelle du travail; ethnologie; fem1000; fem7000; inégalités; lit3220; premier cycle; rapports sociaux de sexe; sciences; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie